Information technology governance for higher education institutions: a multi-country study - Scalabrin Bianchi, Isaías (2021)
Information Technology governance (ITG) calls for the definition and implementation of formal practices at the highest level in the organization, involving structures, processes and relational practices for the creation of business value from IT investments. However, determining the right ITG practices remains a complex endeavor. Previous studies identify IT governance practices used in the health and financial sectors. As universities have many unique characteristics, it is highly unlikely that the ITG experiences of the financial and health industry can be directly applied to universities. This study, using Design Science Research (DSR), develops a baseline with advised practices for the university sector. The analysis of thirty-four case studies from the literature review provides a set of practices as a starting point for the development of the baseline model proposal through multiple case studies involving interviews with IT directors, in ten universities in five countries: eight new practices emerge in this study. The model proposed was evaluated by experts. The result is a baseline model with adequate practices for IT governance in universities as well as a set of guidelines for its implementation. Findings revealed that is possible to extend the ITG practices’ baseline when looking at specific contexts.